2009
DOI: 10.1590/s1516-89132009000500023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different grinding levels (particle size) of soybean hull on starting pigs performance and digestibility

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…For example, fine grinding (3‐mm hammer‐mill screen) elevated ADC of gross energy in pigs compared to coarse grinding with 6‐mm screen (Callan, Garry, & O'Doherty, ). Another pig study demonstrated higher ADCs when using a 3.0‐mm compared to a 2.5‐mm screen mesh with grinding (Moreira et al., ). The ADC of crude protein increased when the grinding screen size increased from 2.0 to 3.0 mm, but it was reduced at a screen size of 3.5 mm (Moreira et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, fine grinding (3‐mm hammer‐mill screen) elevated ADC of gross energy in pigs compared to coarse grinding with 6‐mm screen (Callan, Garry, & O'Doherty, ). Another pig study demonstrated higher ADCs when using a 3.0‐mm compared to a 2.5‐mm screen mesh with grinding (Moreira et al., ). The ADC of crude protein increased when the grinding screen size increased from 2.0 to 3.0 mm, but it was reduced at a screen size of 3.5 mm (Moreira et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another pig study demonstrated higher ADCs when using a 3.0‐mm compared to a 2.5‐mm screen mesh with grinding (Moreira et al., ). The ADC of crude protein increased when the grinding screen size increased from 2.0 to 3.0 mm, but it was reduced at a screen size of 3.5 mm (Moreira et al., ). The improvement of digestibility may result from the increase in the uniformity and the surface area of ingredients (Callan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, feed-processing techniques such as pelleting to increase diet bulk density or fine grinding to improve digestibility of soybean hulls may mitigate its negative growth effects. Moreira et al (2009) found that grinding soybean hulls (751 to 430 µ) increased metabolizable energy (ME) for growing and finishing pigs; however, pig growth performance was not measured in that study.…”
Section: Introductionmentioning
confidence: 80%
“…It was hypothesized that by reducing the particle size of soybean hulls the digestibility would improve. A study from South America by Moreira et al (2009) observed an improvement in digestible energy and ME when soybean hulls were ground through a 2.5-mm screen. However, soybeans are process differently in South America than in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation